Contours of pacificism: Ramsden Balmforth's advocacy of peace in the Union of South Africa and beyond - F. Hale (Acta Theologica)
Among the many dimensions of Christian pacifism in South Africa which remain underexplored is the ministry of the Unitarian minister Ramsden Balmforth (1861-1941). For approximately four decades beginning shortly after his arrival in Cape Town in 1897, this Christian socialist devoted part of his time to efforts to promote peace both in southern Africa and on a broader, almost global, scale. It is argued that Balmforth was not at any time an absolute pacifist, and that the distinction between “pacifism” and “pacificism” which was advanced by inter alia the British historians A.J.P. Taylor and Martin Ceadel is particularly useful for interpreting Balmforth and placing him on the spectrum of positions with regard to the ethical defensibility of taking up arms.